Relationship Between the Lactate-to-Albumin Ratio and 28-Day Overall Mortality in Critically Ill Patients with Pulmonary Embolism: A Retrospective Analysis of the MIMIC-IV Database - Junhao Xu MD; Shaoxing Wu MD; Haipeng Li MD; Xinming Chen MD; You Zhou PhD; Yinji Xu MD (Clinical and Applied Thrombosis/Hemostasis)
Background The lactate-to-albumin ratio (LAR) has prognostic value in various clinical conditions, but its association with mortality in pulmonary embolism (PE) remains unclear. This study aims to investigate the relationship between LAR and 28-day all-cause mortality in PE patients. Methods This retrospective observational study used MIMIC-IV database, with 28-day mortality as the primary endpoint. Adjusted Cox models were used to assessed the LAR-mortality association, with subgroup analyses for stability. Kaplan-Meier curves estimated mortality across LAR tertiles. Restricted cubic spline(RCS) analysis evaluated nonlinearity. Receiver operating characteristic curves(ROC) and reclassification metrics were used to compare the predictive performance of LAR with the Pulmonary Embolism Severity Index (PESI). Results Among the 319 included patients, 72 (22.6%) died within 28 days of admission. Non-survivors had significantly higher LAR levels. In adjusted Cox models, elevated LAR was independently associated with increased 28-day mortality risk. Kaplan-Meier curves showed significant survival differences across LAR tertiles. RCS analysis revealed a dose-response relationship with an inflection point around LAR 0.67. The ROC curve's C-statistic, validated by the DeLong test, highlights the superior performance of the LAR model, while the positive Integrated Discrimination Improvement and Net Reclassification Improvement values demonstrate its additional prognostic value over the PESI model. Subgroup analysis confirmed consistent findings across different patient groups. Conclusion Elevated LAR was positively correlated with 28-day all-cause mortality in PE patients, maintaining prognostic value across subgroups. LAR showed potential as a practical prognostic indicator for PE risk stratification, warranting prospective validation and exploration of its clinical utility in PE management.